2016
DOI: 10.1371/journal.ppat.1005896
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Effects of an Immunodominant Parasite Antigen Paradoxically Prevent Induction of Optimal CD8 T Cell Protective Immunity

Abstract: Trypanosoma cruzi infection is controlled but not eliminated by host immunity. The T. cruzi trans-sialidase (TS) gene superfamily encodes immunodominant protective antigens, but expression of altered peptide ligands by different TS genes has been hypothesized to promote immunoevasion. We molecularly defined TS epitopes to determine their importance for protection versus parasite persistence. Peptide-pulsed dendritic cell vaccination experiments demonstrated that one pair of immunodominant CD4+ and CD8+ TS pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…Emerging results have revealed that vaccines that strictly elicit immunodominant epitope-specific CTL responses could be more effective against viruses. Vaccines that induce both immunodominant and subdominant epitope responses were significantly less protective than vaccines that only elicited immunodominant epitope-specific responses, suggesting that the increased breadth of T-cell epitope recognition may prevent the induction of optimal protective CTL immunity and reduce the efficiency of host immunity against pathogens ( 43 , 44 ). The secondary CTL expansion in vaccinated mice competes for antigen accessibility on antigen-presenting cells, suppressing the priming of other protective pathogen-specific CTLs ( 45 ) and potentially explaining how subdominant epitope vaccination could reduce immunodominant epitope-induced CTL responses.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging results have revealed that vaccines that strictly elicit immunodominant epitope-specific CTL responses could be more effective against viruses. Vaccines that induce both immunodominant and subdominant epitope responses were significantly less protective than vaccines that only elicited immunodominant epitope-specific responses, suggesting that the increased breadth of T-cell epitope recognition may prevent the induction of optimal protective CTL immunity and reduce the efficiency of host immunity against pathogens ( 43 , 44 ). The secondary CTL expansion in vaccinated mice competes for antigen accessibility on antigen-presenting cells, suppressing the priming of other protective pathogen-specific CTLs ( 45 ) and potentially explaining how subdominant epitope vaccination could reduce immunodominant epitope-induced CTL responses.…”
Section: Discussionmentioning
confidence: 99%
“…The amplified sequence was cloned into the pGEM ® -T easy vector (Promega, USA) using a T4 DNA Ligase enzyme (Promega, USA) at 4°C overnight. Then, the plasmids were transformed in E. coli DH5α competent cells as previously described [ 49 ] and mini preparations of pGEM°-T easy vector were obtained using Miniprep isolation columns (QIAGEN, Valencia, CA), following the manufacturer's instructions. After sequencing the plasmids, the identity of the PCR products was verified by alignment with all the TS genes indexed in the GenBank and the particular sequence (AJ276679) that was used to design the primers.…”
Section: Methodsmentioning
confidence: 99%
“…These authors propose that even though the naturally-triggered immunity to T. cruzi is strong, vaccination could be exploited to induce CD8 + T cells of improved quality and fitness to cope with the infection. Moreover, a combination of genetic and cell-based immunization approaches allowed to obtain important data related to epitope immunodominance [76]. These authors showed that a DNA vaccine encoding an enzymatically active TS and an immunodominant CD8 + T cell epitope is able to enhance subdominant pathogen-specific CD8 + T cell responses as consequence of a co-stimulatory effect mediated by active TS.…”
Section: Vaccinesmentioning
confidence: 99%